LOW-LEVEL LASER THERAPY AS A FORM OF TREATMENT FOR LOW BACK PAIN: AN INTEGRATIVE REVIEW - Filoni, Eduardo; Filho, Alfredo Ribeiro; Pardi, Paulo Celso; Braga, Cristina; Cavalcante, Fabrício Vieira; Crozariol, Clayton Gomes; Isabella, Adriana Paula Jordão; Salani, Renata; Olímpio, Aloísio; Capeloa, Cristina Nunes; Douradinho, Christian; Ocon, Carlos Alberto; et al. (Seven Editora, 2024)
Introduction: Low back pain is an important cause of disability, occurring in high prevalence in all cultures, negatively influencing people’s quality of life. The low-level laser has been shown to be an appropriate choice for reducing pain. The objective of the present study was to evaluate the use of low-level laser in low back pain. Method: Integrative review using articles in Lilacs, Medline, Scielo, Cochrane Library and journals. The inclusion criteria for the clinical studies in this review were: being a randomized clinical study investigating the effect of low-level laser on low back pain, alone or as part of a treatment program; assess at least one of the following outcomes: pain, disability, and quality of life. Studies located in the period from 2013 to 2033 were included. Results and Discussion: The studies showed the role of LLLT in reducing inflammation, changing endorphin levels, reducing pain, and accelerating recovery of nerve conduction. Final Considerations: Most of the articles showed favorable effects of low-level laser on low back pain with adjuvant therapies. DOI:https://doi.org/10.56238/sevened2024.037-060